Method for preparing iron oxyhydroxide

JP7634687B2Active Publication Date: 2025-02-21LANXESS DEUTSCHLAND GMBH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023538120
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-21
Filing Date
2021-12-08
Publication Date
2025-02-21
Estimated Expiration
2041-12-08

Smart Images

  • Figure 0007634687000001
    Figure 0007634687000001
  • Figure 0007634687000002
    Figure 0007634687000002
Patent Text Reader

Abstract

The present invention relates to a method for preparing iron oxyhydroxide by adding an aqueous iron salt solution (A) and an aqueous alkaline precipitant solution (B) to an initial charge while maintaining the pH in the range of 6-10.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for preparing iron oxyhydroxide. [Background technology]

[0002] Iron oxyhydroxides, obtained by precipitation of iron(III) salts with alkaline precipitants or by precipitation of iron(II) salts with alkaline precipitants and subsequent oxidation, have many applications as color pigments. However, other applications, such as use as catalysts for producing adsorbents or polymers, are also known. Especially when used as catalysts, high demands are made on the by-product spectrum.

[0003] The precipitation of iron oxyhydroxide is described, for example, in US Pat. No. 5,399,433, where an iron(III) sulfate solution is specified and NaOH is added as precipitant, or vice versa. Amorphous iron(III) hydroxide can be reached, for example, by the following synthetic route: Fe2(SO4)3+6NaOH→2Fe(OH)3+3Na2SO4

[0004] According to the method described in (Patent Document 1), the NaOH precipitant is charged first and the iron salt is added thereto, whereby the iron oxyhydroxide is obtained as a product with a very high Na content. If proceeding in the opposite manner, and the NaOH precipitant is added to the iron salt charged first, the iron oxyhydroxide is obtained as a product with a very high sulfur content. However, the iron oxyhydroxide prepared by both variants has excessive sodium and / or sulfur contents, especially for catalytic applications, which cannot be significantly reduced in any case even by multiple washings.

[0005] The preparation of iron oxyhydroxide starting from an initially charged iron(II) sulfate solution by addition of NaOH and subsequent oxidation with air also leads to iron oxyhydroxide with excessive sodium and sulfur contents which cannot be significantly reduced by multiple washings. A corresponding process is described, for example, in US Pat. No. 5,399,363.

[0006] In this case, white Fe(OH)2 precipitates from the iron(II) salt solution by the addition of an alkaline aqueous solution, with the exclusion of air. Oxidation then takes place in air, through greyish-green, dark green, and blackish intermediate stages. When Fe(OH)2 is oxidized, a mostly crystalline phase is obtained, but when the iron(III) salt solution is mixed with hydroxide, Fe(OH)3 is formed in amorphous form.

[0007] In this case, iron(III) hydroxide, Fe(OH), typically precipitates as a water-containing hydrogel of formula FeO·nHO ("iron(III) oxyhydrate").

[0008] Ion [Fe(H2O)6] 3+ is stable at pH levels below 0 and is yellow-brown in pH levels between 0 and 2, [Fe(OH)(H2O)5] 2+ , [Fe(OH)2(H2O)4] at pH 2-3 + and polynuclear complexes, e.g. [ka] At pH 3-5, it is converted to a polynuclear isopolyoxocation. Further polymerization produces reddish-brown colloidal spherical polynuclear species. The water-containing hydrogel is amorphous and structureless, which is due to the central Fe 3+ Anion to Cation (OH - ) and (O 2- ) there is local near-neighborhood order but no long-range order, meaning that there is no regular repetition in three dimensions of space of the structural elements that form the crystal lattice.

[0009] Therefore, the term "bilinear ferrihydrite", often specified as the formula Fe2O3·nH2O to record the uncertain water content, has also been established in the literature [(Non-Patent Document 1)].

[0010] It consists of mostly amorphous iron hydroxide, which shows two very broad signals in the X-ray powder diffractogram. 2The specific surface area of ​​the sample can be measured by the BET method in g / g. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] European Patent Application Publication No. 1582505A1 [Patent Document 2] International Publication No. 02 / 026632 Brochure [Non-patent literature]

[0012] [Non-Patent Document 1] U. Schwertmann, RM Cornell, Iron Oxides in the Laboratory, pp.103-112, Wiley-VCH, 2000 Summary of the Invention [Problem to be solved by the invention]

[0013] In the known methods, iron salts or precipitants as well as sulfur in the form of sulfates and sodium ions resulting from the corresponding reactions are tightly integrated into the iron hydroxide lattice and cannot be completely removed even by extensive washing with demineralized washing solutions. In the case of other iron sources, such as iron(III) chloride, the chlorine content is also difficult to reduce, which is undesirable in most cases due to its tendency to corrosion.

[0014] For example, when precipitation is carried out starting from iron(III) chloride, the β-FeOOH phase (akaganeite) is preferably formed, which, due to its particular structure, has a high chloride content. The same applies to the anions of other iron sources and cations of the precipitating agent.

[0015] It was therefore an object of the present invention to provide a process which allows for an iron oxyhydroxide having the lowest possible content of cations, in particular alkali metals and / or alkaline earth metals, originating from the precipitating agent and at the same time the lowest possible content of anions, in particular sulfur and / or chloride, originating from the iron salt. [Means for solving the problem]

[0016] method Accordingly, the present invention provides a method for preparing iron oxyhydroxide, comprising the steps of: i) an aqueous iron salt solution (A) and an aqueous alkaline precipitant solution (B), preferably an alkali metal hydroxide solution, are mixed with each other, the mixing being carried out in such a way that the pH of the mixture formed in the initial charge is maintained in the range of 6 to 10 throughout the addition of (A) and (B); ii) when an aqueous iron salt solution (A) of an Fe(II) salt is used, during or after mixing of (A) with (B) an oxygen-containing gas is introduced for oxidation of Fe(II) to Fe(III); iii) the suspension obtained after step i) or ii) is separated from the solids, iv) the solid obtained after step iii), in particular the filter cake, is washed with demineralized (DM) water, preferably to a filtrate conductivity of less than 2000 μS / cm; and v) drying the washed solid after step iv). The present invention relates to a method characterized by the above. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Iron oxyhydroxide The iron oxyhydroxides prepared by the method of the present invention include crystalline forms such as FeO, Fe2O3, Fe3O4, and FeOOH, as well as amorphous forms such as Fe(OH)3 and its water-containing hydrogels.

[0018] Process i) Iron salt solution (A) The iron salt of the aqueous iron salt solution (A) used can be both an iron (II) salt and an iron (III) salt. The iron (III) salt is preferred, in which case preferably iron (III) sulfate, iron (III) nitrate, iron (III) chloride, iron (III) phosphate, iron (III) chloride sulfate, or any other iron (III) salt can be used. Preference is given to iron (III) sulfate or iron (III) chloride.

[0019] In the case of iron(II) salts, preferably iron(II) sulfate, iron(II) nitrate, iron(II) chloride, iron(II) phosphate or any other iron(II) salt may be used, with preference given to iron(II) chloride or iron(II) sulfate.

[0020] Depending on the anion used in the process according to the invention, the residual proportions thereof can be very significantly reduced in the resulting iron oxyhydroxide, typically measured, for example, as the sulfur content for sulfates, preferably as the chloride content for chlorides, and as the nitrate content for nitrates.

[0021] The aqueous iron salt solution (A) preferably contains 10 to 1000 g / L, preferably 50 to 800 g / L, of iron salt, based on the aqueous iron salt solution (A). Besides water, the solution may also contain an organic solvent, for example aliphatic solvents such as methanol, ethanol, propanols such as isopropanol, butanols or others may be mentioned as organic solvents.

[0022] Based on the total content of solvents in the iron salt aqueous solution (A), the proportion of water is preferably 90-100% by weight, preferably 99-100% by weight.

[0023] Alkaline precipitant aqueous solution (B) The precipitant of the aqueous alkaline precipitant solution (B) is, for example, an alkali metal or alkaline earth metal hydroxide, and those particularly used are alkali metal or alkaline earth metal carbonates such as NaOH or KOH or Ca(OH)2, Na2CO3, K2CO3, CaCO3 or MgCO3, alkaline earth metal oxides such as MgO or CaO, or NH3 or NH4OH. Component (B) is preferably an alkali metal hydroxide solution.

[0024] The aqueous alkaline precipitant solution (B) preferably contains 10 to 600 g / L, preferably 50 to 440 g / L, of precipitant, based on the solution. Besides water, the solution may also contain organic solvents, for example aliphatic solvents such as methanol, ethanol, propanols such as isopropanol, butanols or others may be mentioned as organic solvents.

[0025] Based on the total content of solvents in the precipitant aqueous solution (B), the proportion of water is preferably 90-100% by weight, preferably 99-100% by weight.

[0026] The initial charge, to which both solutions (A) and (B) are added, is preferably an empty vessel or a vessel containing water. The pH can be measured in the reaction mixture, preferably in the reaction suspension, by a pH probe. Mixing can be performed already during the addition, for example by mixing elements for the addition stream, or only during the initial charge, for example by mixing elements attached thereto. Stirrers or static mixers are suitable as conventional mixing elements. During the addition to the initial charge, air can also be introduced as an aid for thorough mixing. This can also be the case when using Fe(III) salts that do not need to be oxidized during or after the addition.

[0027] Components (A) and (B) may be added continuously or in portions to the initial charge.

[0028] To measure the pH, any commercially available pH probe can be used.

[0029] Both components (A) and (B) are preferably added such that the addition of the two components (A) and (B) maintains the pH in the range of 6 to 10, in particular 6.5 to 9.5, during the addition. The addition is preferably carried out at the selected pH within a deviation range of ±0.5 pH units.

[0030] Since the pH generally changes more drastically at the beginning of the addition relative to the starting pH of the initial charge, the pH value usually does not stabilize around a certain value unless after a short initial period. The pH is therefore preferably adjusted within a specific range so that it is within said range for 95% of the entire period of addition of A) and B) to the initial charge, in particular so that the desired pH is preferably within a deviation range of ±0.5 pH units. The iron salt solution (A) is preferably added to the initial charge continuously, preferably at a constant addition rate, and the precipitant solution (B) is added so that the desired pH can be maintained within a specified range.

[0031] In this case, during the addition of A) and B) to the initial charge, variations in the addition from the respective desired stoichiometric ratio of the two components may occur, so that deviations from the respective desired stoichiometric ratio of up to 10% of the stoichiometry during the addition are quite common.

[0032] Mixing is preferably carried out at any temperature level, in particular at temperatures between 10 and 100°C.

[0033] After mixing components (A) and (B), an aqueous suspension of iron oxyhydroxide is obtained. The resulting solid particles preferably have a density of 50 to 400 g / m 2 , preferably 50 to 300 g / m 2 has a BET surface area of

[0034] Process ii) When an iron salt in oxidation state +2 is used, oxygen or an oxygen-containing gas, in particular air, is preferably added already during the mixing of the two components A) and B. This is preferably carried out by introducing oxygen or an oxygen-containing gas into the initial charge throughout the addition of both components. Oxygen or an oxygen-containing gas may also be introduced into the initial charge after the addition of the two components A) and B).

[0035] Process iii) The aqueous suspension obtained after step i) or ii) is preferably separated from the solids by filtration, e.g. by filtration through a filter press, or by centrifugation.

[0036] Process iv) The solid obtained after step iii), in particular the filter cake, is preferably washed with demineralized (DM) water, preferably to a filtrate conductivity of less than 1000 μS / cm, in particular less than 300 μS / cm, particularly preferably less than 100 μS / cm. The measurement of the filtrate conductivity is in this case measured by a conventional conductivity measuring device.

[0037] Process v) The solid obtained after washing according to step iv) is typically dried at a temperature of 60 to 300° C., in particular 60 to 100° C. Conventional pigment dryers are suitable as dryers. The solid is preferably dried to a residual moisture of less than 1% by weight of water, based on the solid.

[0038] Drying may be followed by grinding, for example to achieve dispersion of agglomerates and aggregates, which may be advantageous, for example to allow homogeneous distribution in the application medium. EXAMPLES

[0039] Comparative Example 1 (=Comparative 1) (similar to Example 1 of EP 1582505) 15 L of Fe2(SO4)3 solution with a Fe2(SO4)3 content of 107 g / L was initially charged at 50° C. and precipitated with 3.5 L of NaOH solution (302 g / L) at an addition rate of 67 g / min to pH 7 with stirring, and the mixture was post-stirred for 30 min. The resulting final suspension contained 37 g / FeOOH.

[0040] Approximately 5 L of the resulting suspension was washed with DM water in a laboratory filter press to a filtrate conductivity of less than 100 μS / cm. The filter cake was dried at 75° C. in an air-circulating drying cabinet and the dried iron hydroxide was lightly ground in a laboratory grinder. Elemental analysis See Table 1

[0041] Comparative Example 2 (=Comparative Example 2) (similar to Example 1 of EP 1582505) 15 L of Fe2(SO4)3 solution (107 g / L) was initially charged at 50°C and precipitated with 3.4 L of NaOH solution (309 g / L) at an addition rate of 65 g / min with stirring until pH 8, and the mixture was post-stirred for 30 min. The resulting final suspension contained 37 g / L FeOOH.

[0042] Approximately 5 L of the resulting suspension was washed in a Nutsche filter to a filtrate conductivity of 146 μS / cm, the resulting filter cake was dried at 75° C. in an air-circulating drying cabinet, and the dried iron hydroxide was crushed in a laboratory coarse grinder. Elemental analysis See Table 1

[0043] Comparative Example 3 (=Comparative Example 3) (similar to Example 3 of EP 1582505) 16 L of NaOH solution (60 g / L NaOH) was initially charged and heated with stirring to 50° C. Then, at free temperature level, 2.4 L of Fe2(SO4)3 solution (107 g / L Fe2(SO4)3) was added at an addition rate of 65 g / min up to pH 9.

[0044] The mixture was stirred for an additional 15 min.

[0045] The batch was then washed in a laboratory filter press to a filtrate conductivity of less than 100 μS / cm. The filter cake was dried in an air circulating drying cabinet at 75° C. to constant weight and the solid was lightly ground in a laboratory grinder. Weight: 301g solid Elemental analysis See Table 1

[0046] Example 1 (present invention) 12186 g of demineralized (DM) water was initially charged and heated with stirring to 50° C. Then, at free temperature level, 4200 g of Fe2(SO4)3 solution (637 g / L, 42% Fe2(SO4)3) was added at an addition rate of 32 g / min, and the pH was maintained at 7.0 by simultaneous addition of NaOH solution (313 g / L NaOH).

[0047] The resulting suspension was washed in a laboratory filter press to a filtrate conductivity of less than 90 μS / cm. The filter cake was dried in an air circulating drying cabinet at 75° C. and the dried solid was lightly ground in a laboratory grinder. Weight: 640g solid Analysis: FeOOH content in suspension = 39.7 g / L; BET = 93 m 2 / g Elemental analysis See Table 1.

[0048] Example 2 (present invention) 12186 g of DM water was initially charged and heated with stirring to 50° C. Then, at free temperature level, 4200 g of Fe2(SO4)3 solution (637 g / L, Fe2(SO4)3) was added at an addition rate of 32 g / min, and the pH was maintained at 8.0 by simultaneous addition of NaOH solution (313 g / L NaOH).

[0049] The resulting suspension was washed in a laboratory filter press to a filtrate conductivity of less than 90 μS / cm. The filter cake was dried in an air circulating drying cabinet at 75° C. and the dried solid was lightly ground in a laboratory grinder. Weight: 681g solid Analysis: FeOOH content in suspension = 51.6 g / L; BET = 126 m 2 / g Elemental analysis See Table 1

[0050] Example 3 (present invention) 12186 g of DM water was initially charged and heated with stirring to 50° C. Then, at free temperature level, 4200 g of Fe2(SO4)3 solution (637 g / L, Fe2(SO4)3) was added at an addition rate of 32 g / min, and the pH was maintained at 8.5 by simultaneous addition of NaOH solution (313 g / L NaOH).

[0051] The resulting suspension was washed in a laboratory filter press to a filtrate conductivity of less than 90 μS / cm. The filter cake was dried in an air circulating drying cabinet at 75° C. and the dried solid was lightly ground in a laboratory grinder. Weight: 661g solid Analysis: FeOOH content in suspension = 42.4 g / L; BET = 152 m 2 / g Elemental analysis See Table 1

[0052] Example 4 (present invention) 12186 g of DM water was initially charged and heated with stirring to 50° C. Then, at free temperature level, 4200 g of Fe2(SO4)3 solution (637 g / L, Fe2(SO4)3) was added at an addition rate of 32 g / min, while the pH was maintained at 9.0 by simultaneous addition of NaOH solution (313 g / L NaOH).

[0053] The resulting suspension was washed in a laboratory filter press to a filtrate conductivity of less than 90 μS / cm. The filter cake was dried in an air circulating drying cabinet at 75° C. and the dried solid was lightly ground in a laboratory grinder. Weight: 660g solid Analysis: FeOOH content in suspension = 41.1 g / L; BET = 177 m 2 / g Elemental analysis See Table 1

[0054] Example 5 (present invention) 12055 g of DM water was initially charged and heated with stirring to 50° C. Then, at free temperature level, 4167 g of FeCl3 solution (517 g / L FeCl3) was added at an addition rate of 28 g / min, while the pH was maintained at 8.0 by simultaneous addition of KOH solution (420 g / L KOH).

[0055] The suspension was washed in a laboratory filter press to a filtrate conductivity of less than 90 μS / cm. The filter cake was dried in an air circulating drying cabinet at 75° C. and the dried solid was lightly ground in a laboratory grinder. Weight: 656g solid Analysis: FeOOH content in suspension = 40.6 g / L; BET = 162 m 2 / g Elemental analysis See Table 1

[0056] Example 6 (present invention) 10840 g of DM water was initially charged with stirring at 25° C. Then, at free temperature level, 7205 g of FeSO4 solution (249 g / L FeSO4) was added at an addition rate of 100 g / min, and the pH was maintained at 8.5 by simultaneous addition of NaOH solution (313 g / L NaOH). 800 L / h of air was also added simultaneously with the addition of the NaOH solution.

[0057] The resulting suspension was washed in a laboratory filter press to a filtrate conductivity of less than 90 μS / cm. The filter cake was dried in an air circulating drying cabinet at 75° C. and the dried solid was lightly ground in a laboratory grinder. Weight: 704g solid Analysis: FeOOH content in suspension = 38.7 g / L; BET = 121 m 2 / g Elemental analysis See Table 1

[0058] Example 7 (present invention) 10840 g of DM water was initially charged with stirring at 25° C. Then, at free temperature level, 7205 g of FeSO4 solution (249 g / L FeSO4) was added at an addition rate of 100 g / min, and the pH was maintained at 9.0 by simultaneous addition of NaOH solution (313 g / L NaOH). 800 L / h of air was also added simultaneously with the addition of the NaOH solution.

[0059] The resulting suspension was washed in a laboratory filter press to a filtrate conductivity of less than 90 μS / cm. The filter cake was dried in an air circulating drying cabinet at 75° C. and the dried solid was lightly ground in a laboratory grinder. Weight: 707g solid Analysis: FeOOH content in suspension = 39.8 g / L; BET = 121 m 2 / g Elemental analysis See Table 1

[0060] [Table 1]

Claims

1. 1. A method for preparing iron oxyhydroxide comprising the steps of: i) an aqueous iron salt solution (A) and an aqueous alkaline precipitant solution (B) are mixed with each other by simultaneous addition of (A) and (B), said mixing being carried out in such a way that the pH of the mixture formed in the initial charge is maintained in the range of 6 to 10 throughout the addition of (A) and (B); ii) when an aqueous Fe(II) salt solution (A) is used, during or after said mixing of (A) and (B) an oxygen-containing gas is introduced for oxidation of Fe(II) to Fe(III); iii) the suspension obtained after step i) or ii) is separated from the solids; iv) the solid obtained after step iii) is washed with DM water; and v) drying the solid obtained after step iv). The method comprising:

2. 2. The process according to claim 1, characterized in that the iron salt of the aqueous iron salt solution (A) used is an Fe(III) salt.

3. 3. The process according to claim 1, wherein the iron salt of the aqueous iron salt solution (A) used is iron(III) sulfate.

4. 4. The process according to claim 1, wherein the aqueous alkaline precipitant solution (B) used is an aqueous alkali metal hydroxide solution.

5. 5. The method according to claim 1, wherein the mixing is carried out in such a way that the pH of the mixture formed in the initial charge is maintained at 6.5 to 9.5.

Citation Information

Patent Citations

  • Stable adsorber granulates

    EP1582505A1

  • Fine acicular alpha-ferric oxide and production thereof

    JP1995206446A

  • Method for producing iron oxyhydroxide particle

    JP2008239399A

  • Stable adsorber granule

    JP2012071305A

  • Contact body and adsorbent granules

    JP2012161797A